Nebulized isotonic saline improves voice production in Sjögren's syndrome. (17th March 2015) - Tanner, Kristine; Nissen, Shawn L.; Merrill, Ray M.; Miner, Alison; Channell, Ron W.; Miller, Karla L.; Elstad, Mark; Kendall, Katherine A.; Roy, Nelson
Abstract : Objective: This study examined the effects of a topical vocal fold hydration treatment on voice production over time. Study Design: Prospective, longitudinal, within‐subjects A (baseline), B (treatment), A (withdrawal/reversal), B (treatment) experimental design. Methods: Eight individuals with primary Sjögren's syndrome (SS), an autoimmune disease causing laryngeal dryness, completed an 8‐week A‐B‐A‐B experiment. Participants performed twice‐daily audio recordings of connected speech and sustained vowels and then rated vocal effort, mouth dryness, and throat dryness. Two‐week treatment phases introduced twice‐daily 9‐mL doses of nebulized isotonic saline (0.9% Na + Cl − ). Voice handicap and patient‐based measures of SS disease severity were collected before and after each 2‐week phase. Connected speech and sustained vowels were analyzed using the Cepstral Spectral Index of Dysphonia (CSID). Acoustic and patient‐based ratings during each baseline and treatment phase were analyzed and compared. Results: Baseline CSID and patient‐based ratings were in the mild‐to‐moderate range. CSID measures of voice severity improved by approximately 20% with nebulized saline treatment and worsened during treatment withdrawal. Posttreatment CSID values fell within the normal‐to‐mild range. Similar patterns were observed in patient‐based ratings of vocal effort and dryness. CSID values and patient‐based ratings correlated significantly ( P  < .05). Conclusion: Nebulized isotonic saline improves voice production based on acoustic and patient‐based ratings of voice severity. Future work should optimize topical vocal fold hydration treatment formulations, dose, and delivery methodologies for various patient populations. This study lays the groundwork for future topical vocal fold hydration treatment development to manage and possibly prevent dehydration‐related voice disorders. Level of Evidence: 2b. Laryngoscope, 125:2333–2340, 2015